A sobrevivência das culturas como prescrição ética para o planejamento cultural: um estudo conceitual - Fernandes, Diego Mansano [UNESP] (2015)
B. F. Skinner develop a behavioral analysis of value, describing what he calls goods or reinforcing consequences that control human behavior: the good of the individual, the good of others, and the good of the culture. Beyond this description, Skinner prescribed the good of the culture, or the survival of the cultures as a value that we should pursue. Through the epistemological hermeneutic method, this study sought a conceptual analysis to Skinner's ethic prescription concerning the role of the behavior analyst in designing a cultura, and also as a strategy to develop a behavioral analysis of culture. The first step was to the search for a definition of culture, by an incursion in Anthropology and fundamentally in Radical Behaviorism. It is argued that culture can be defined based on Skinner's works as social environment, but also in a strict sense as a social experiment, and, with some controversies, in a broader sense as a set of cultural practices. Concerning Anthropology, the skinnerian idea of culture proved aligned with modern versions for the concept in the field especially for its ontology and its denial of dicthotomies like natural and culture, and a pluralist wordwiew. It folllows that on the presented definitions of culture, the prescription of the survival of the cultures in a broader sense proved frail and difficult to instrumentalize, because it implies divergences and competition between social and verbal environments, with contradictory and unsuitable structures and cultural practices. Such conflicts delivery sharp results in daily life, like prejudices and discriminations of gender, race, class, sexual orientation, linguistic and so on. Some of Skinner's proposals in the political scope are suggested as more promissing, especially the design of social environments based on face-to-face control, by the people and for the people